Study the Antibacterial Activity of Bauhinia variegata Linn. plant Leaf Extracts Against Some Species of Pathogenic Bacteria - Rashid, Khaleel Ibrahim; Ahmmed, Shayma Jamal; Mahmood-Mukhtar, Zaynab Farkad (Al-Nahrain Journal of Science, 2018)
Microbial resistance to antibiotics is highly increasing during the three last decades. Evaluation of natural products to access new and effective antimicrobial agents is one of the scientific strategies to combat drug-resistant pathogens. With this perspective, leaf extracts of Bauhinia vareigata which had documented uses in traditional medicine, were investigated for antimicrobial activity against four bacterial strains, two gram-positive ; Staphylococcus aureus, Streptococcus pyogenes. and two gram-negative; Escherichia coli, Proteus mirabilis. The antimicrobial activity was evaluated by measuring inhibition zone diameters in agar well diffusion assay. The aim of the present study was to evaluate the antimicrobial potential of B.variegata leaves extract as compared with antibiotics such as ampicillin, so that this medicinal plant could serve as a good candidate to treat various infectious diseases. The crude extracts of Bauhinia variegata showed high antibacterial activity against all bacterial strains as compared with the antibiotic ampicilliwhich recorded inhibition zone ranged from 21 mm to 34 mm. Ethanol diluted extract revea n led no activity at the dilutions from 2% to 16%, while it showed less activity at the dilutions of 32% and 64% against staphylococcus aureus, Streptococuus pyogenes and Proteus mirabilis. Escherichia coli showed resistance against all extract dilutions. It was noted that the extracts were more active against Proteus mirabilis, as compared with other bacterial species. Finally, all the bio-extracts were well stable at room temperature during the duration of the study and did not show any reduction of activity against the bacterial strains used in this study experiments.